2014
DOI: 10.5551/jat.22186
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A-enriched Diet Modulates Reverse Cholesterol Transport in Hypercholesterolemic Obese Rats of the WNIN/Ob Strain

Abstract: Aim: Vitamin A plays a major role in lipid metabolism. Previously, we reported that chronic vitamin A feeding (129 mg/kg) for two months normalized the abnormally high plasma HDL-cholesterol (HDL-C) levels in hypercholesterolemic obese rats by upregulating the hepatic scavenger receptor class B type 1 (SR-BI) expression. In this report, we hypothesize that the administration of a dose less than 129 mg of vitamin A/kg would also be effective in lowering the plasma HDL-C levels in these rats. Methods: Changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The vitamins (A, D, and E) and carotenoids in CDAI are fat-soluble and vitamin C is water-soluble, which is relevant for absorption, transport and action. Feeding a VA-rich (52 mg/kg) diet for 20 weeks in hypercholesterolemic obese rats increased plasma lecithin cholesterol acyltransferase activity and expression of ATP-binding cassette transporter protein A1, which, in turn, led to normalization of plasma HDL-C levels ( 43 ). Vitamin C (VC) is an essential nutrient for humans and the effect of administration is highly dose dependent ( 44 ), maximizing neutrophil concentration, reducing ROS production and inhibiting LDL-C oxidation through dietary intake ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The vitamins (A, D, and E) and carotenoids in CDAI are fat-soluble and vitamin C is water-soluble, which is relevant for absorption, transport and action. Feeding a VA-rich (52 mg/kg) diet for 20 weeks in hypercholesterolemic obese rats increased plasma lecithin cholesterol acyltransferase activity and expression of ATP-binding cassette transporter protein A1, which, in turn, led to normalization of plasma HDL-C levels ( 43 ). Vitamin C (VC) is an essential nutrient for humans and the effect of administration is highly dose dependent ( 44 ), maximizing neutrophil concentration, reducing ROS production and inhibiting LDL-C oxidation through dietary intake ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…ey compared the serum levels of vitamin A in 110 patients with severe obesity with that in 58 healthy people and found that the levels of vitamin A in obese patients were significantly lower than those in the healthy controls [38]. Studies found that feeding fat rats with a vitamin A-supplemented diet could correct insulin resistance, plasma high-density lipoprotein level, and hypercholesterolemia in obese rats [39,40]. In addition, the role of retinoic acid in inhibiting adipogenesis in vitro was confirmed in 3T3-L1 cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with either low (52 mg/kg) or high (129 mg/kg) doses of vitamin A affected several players in RCT in obese rats [ 173 ]. Both hepatic SR-BI and ABCA1 proteins were increased in the liver, a dual effect resulting in a decrease of circulating HDL.…”
Section: Effects Of Other Lipids On Rct In Animal Modelsmentioning
confidence: 99%